The Role of Segment Financial Reports in Rationalising Investment Decisions in Iraq - Hamawandy, Nawzad Majeed; Azzat, Rezan Salahaddin; Hamad, Shahla Abdulwahid; Jamil, Diyar bdulmajeed (The journal of contemporary issues in business and government, 2021)
This study investigates the role of financial reports in rationalising investment decisions in Iraq and the corporate stand on disclosure of financial information per the international accounting standards and aims at Demonstrate the Impact of Financial Reports in Rationalizing Investment Decisions, and it has a necessity in disclosure of A Set of Accounting and Financial Information and This Is What Will Help in Making Investment Decisions. The research was conducted through a systemic review methodology whereby a sample of 15 previous studies done on the topic were reviewed and secondary data used for analysis using SPSS. The research found out that sectorial financial reports are incredibly vital in informing the investors while making investment decisions in Iraq. Furthermore, the research found that full disclosure of financial statements, sufficiency, availability of financial reports, and investors' literacy of information in financial reports are vital factors in rationalising investment decisions in Iraq.